Responses of Soybean Genes in the Substituted Segments of Segment Substitution Lines Following a Xanthomonas Infection - Zou, Jianan; Zhang, Zhanguo; Yu, Siyang; Kang, Qinglin; Shi, Yan; Wang, Jinhui; Zhu, Rongsheng; Ma, Chao; Chen, Lin; Wang, Jieqi; Li, Jianyi; Li, Qingying; et al. (Frontiers in Plant Science, 2020)
Bacterial blight, which is one of the most common soybean diseases, is responsible for considerable yield losses. In this study, a novel Xanthomonas vasicola strain was isolated from the leaves of soybean plants infected with bacterial blight under field conditions. Sequencing the X. vasicola genome revealed type-III effector-coding genes. Moreover, the hrpG deletion mutant was constructed. To identify the soybean genes responsive to HrpG, two chromosome segment substitution lines (CSSLs) carrying the wild soybean genome, but with opposite phenotypes following Xanthomonas inoculations, were used to analyze gene expression networks based on RNA sequencing at three time points after inoculations with wild-type Xanthomonas or the hrpG deletion mutant. To further identify the hub genes underlying soybean responses to HrpG, the genes located in the substituted chromosome segments were examined. Finally, a combined analysis with the QTLs for resistance to Xanthomonas identified 35 hub genes in the substituted chromosomal segments that may help regulate soybean responses to Xanthomonas and HrpG. Furthermore, two candidate genes in the CSSLs might play pivotal roles in response to Xanthomonas.